Islam and the governing of Muslims in France: secularism without religion - Peter, Frank (Islam of the global West, 2021)
Will Islam be able to adapt to France's secularity and its strict separation of public and private spheres? Can France accommodate Muslims? In this book, Frank Peter argues that the debate about "Islam" and "Muslims" is not simply caused by ignorance or Islamophobia. Rather, it is an integral part of how secularism is reasoned. 0Islam and the Governing of Muslims in France shows that the understandings of religion that separate it from other aspects of life, such as politics, economy and culture, fail to capture the ways religion has operated and been managed in "secular" societies such as France. This book uncovers the varying rationalities of the secular that have developed over the past few decades in France to "govern Islam", to argue that scholars should instead examine how Islam is managed politically, culturally, and socially. This book includes empirical research in a close analysis of French secularism as it was experienced by Islamic intellectuals and activists living in France from 1989 until the present. It will influence the study of secularism as well as the study of Islam in the French Republic, and reveal new connections between Islamic traditions and secular rationalities